A two-dimensional analytical model for prediction of the radiation heat transfer in open-cell metal foams. (25th January 2016) - Jiang, Z.; Wang, K.; Wu, H.; Wang, Y.; Du, J.
Highlights: A new 2D explicit analytical model is developed to study radiation heat transfer. A new correction factor is introduced to correct the deviation of specific area. The present model has a reasonable precision by comparing with published data. The effects of different control factors on the radiation characteristics are evaluated. Abstract: In this article, a new two-dimensional (2D) explicit analytical model for the evaluation of the radiation heat transfer in highly porous open-cell metal foams is formulated and validated. A correction factor, C, is introduced to correct the deviation of the specific area in a simplified manner. Numerical results are compared with the published experimental data and three-dimensional (3D) model proposed in previous works. It reveals that the present two-dimensional model is proved to be relatively accurate in estimating the radiative conductivity for all the investigated structures. In the current work, the effects of the control parameters, such as the number of order in the iterative procedure, solid emissivity, the temperature difference, shape of solid particle and correction factor on the predictions of radiation characteristics are well discussed.